The effect of confinement on thermal convection and longitudinal macrosegregation in directionally solidified dilute succinonitrile–camphor alloy - Mota, Fatima L. (2023)
Directional solidification experiments were conducted in a succinonitrile–0.24 wt% camphor alloy with an emphasis on the planar front interface temperature dynamics using different sample thicknesses. The interface temperature was found to depend significantly on the thickness due to non-negligible convection effects in the thicker samples. The results were interpreted with the help of an order of magnitude analysis and a boundary layer model, which permitted estimation of the solute macrosegregation profile. The experiments and corresponding analyses performed in this work constitute an experimental characterization of convection effects as a function of sample thickness.